EVALUATION OF EXTERNAL AUDIT ON THE IMPLEMENTATION OF SNI ISO 17025:2017 IN PROVIDING ADDED VALUE TO THE ORGANIZATION - Ratna Mayasari; Robby Marlon Brando; Sari Andarwati (Badan Standardisasi Nasional, 2023)
XYZ Laboratory has main tasks and functions to carry out technology service activities in the field of machine tool technology, production and automation. One kind of technology service to the industry is as a testing laboratory. SNI ISO/IEC 17025:2017 is a testing laboratory standard that is suitable to support the XYZ Laboratory in carrying out technology service tasks in the field of testing. Because the XYZ Laboratory has been accredited by KAN (National Accreditation Committee) as a testing laboratory, the XYZ Laboratory has an obligation to participate in an external audit conducted by KAN. This needs to be done to maintain the quality of testing laboratory services so that they remain in accordance with applicable standards. Considering that this external audit will be carried out routinely as long as it is accredited as a testing laboratory, it is necessary to carry out an analysis regarding the findings that often appear at the XYZ Laboratory. This will be useful for formulating preventive and corrective actions in the future. The research used descriptive qualitative with the research subject was a testing laboratory, which consisted of laboratory management and implementer. Data collection is used in this study through semi-structured interviews with employees who have been directly involved in accreditation at the XYZ Laboratory for the formulation, management and application of SNI IEC/ISO 17025: 2017 and non-conformance sheets from 2019 to 2021 from the results of an external audit by the Accreditation Committee. Evaluation of the results of external audits conducted by KAN during 2019, 2020 and 2021, shows that clause 6.4 Equipment, clause 6.2 Personnel, and clause 7.2 Selection, verification and validation of methods, are clauses that often encounter discrepancies. The discrepancy between clauses 6.4 and 6.2 intersects where frequent employee turnover makes employee competence management not run optimally, as evidenced by the discovery of the competence of several employees who do not comply with competency requirements causing equipment maintenance to be hampered.